The Formation of Moral Values in Early Childhood Education: Mapping, Challenges, and Teacher Requirements Based on Observations in 10 Kindergartens and Nursery Schools in Bantul - Cholimah, Nur; Mutmainnah, Mutmainnah; Prayitno, Prayitno; Cahyaningrum, Eka Sapti (UPI Kampus Cibiru, 2025)
This study aims to identify the moral values taught, the challenges faced, and the needs of teachers in instilling moral values in early childhood education. Using a descriptive qualitative approach, data were collected through observation and interviews with 10 early childhood and kindergarten institutions in Bantul. The findings show that respect, honesty, responsibility, discipline, and empathy are the most dominant values taught through habituation, modeling, and daily routines. Teachers reported challenges such as children’s limited concentration, behavioral diversity, and low family involvement, and emphasized the need for continuous training, innovative teaching, and stronger collaboration with parents. These challenges arise from the unique developmental characteristics of early childhood and the lack of consistency between school and family moral education. Therefore, contextual and engaging learning strategies are needed to ensure effective internalization of moral values. This study highlights the teacher’s role as a model and facilitator of character development and the importance of parent collaboration. Its impact provides practical insights for educators and policymakers to design integrated, family-based moral education programs that strengthen children’s character formation from an early age.